Nevirapine induced mitochondrial dysfunction in HepG2 cells - Paemanee, Atchara (Sci Rep, 2017)
Nevirapine (NVP) is a non-nucleoside reverse transcriptase inhibitor frequently used in combination with other antiretroviral agents for highly active antiretroviral therapy (HAART) of patients infected with the human immunodeficiency virus type 1 (HIV-1). However NVP can cause serious, life-threatening complications. Hepatotoxicity is one of the most severe adverse effects, particularly in HIV patients with chronic hepatitis C virus co-infection as these patients can develop liver toxicity after a relatively short course of treatment. However, the mechanism of NVP-associated hepatotoxicity remains unclear. This study sought to investigate the effect of NVP on protein expression in liver cells using a proteomic approach. HepG2 cells were treated or not treated with NVP and proteins were subsequently resolved by two-dimensional gel electrophoresis. A total of 33 differentially regulated proteins were identified, of which nearly 40% (13/33) were mitochondrial proteins. While no obvious differences were observed between NVP treated and untreated cells after staining mitochondria with mitotracker, RT-PCR expression analysis of three mitochondrially encoded genes showed all were significantly up-regulated in NVP treated cells. Mitochondrial dysfunction was observed in response to treatment even with slightly sub-optimal therapeutic treatment concentrations of NVP. This study shows that NVP induces mitochondrial dysregulation in HepG2 cells.